(untitled) (Global Journal of Science Frontier Research, 2023)
We present the results of numerical calculations of DT fusion modes in an experimental stellarator reactor operating under conditions of neoclassical transport processes taking into account recycling and the contribution of anomalous losses in the form of Bohm diffusion The calculations were performed in the reactor with relatively small helical magnetic field corrugations when the effective values of helical magnetic field in homogeneity are less than toroidal in homogeneity eff t Using a numerical code a system of equations that describes the spatiotemporal behavior of plasma in a stellarator reactor under conditions of equal diffusion fluxes was considered The influence of Bohm diffusion with a reduced coefficient of proportionality was taken into account The reactor was modeled using heating sources with a capacity of tens of megawatts to bring it into a steady-state self-sustaining reaction mode Stable modes of a self-sustaining fusion reaction were obtained while maintaining the plasma density at a constant level by simulating the injection of DT-fuel pellets into the plasma